Suture granuloma mimicking a recurrent sacro‐coccygeal pilonidal sinus after Limberg flap. Issue 6 (14th August 2014) - Ardelt, Michael; Dittmar, Yves; Schulz, Birte; Rauchfuss, Falk; Scheuerlein, Hubert; Settmacher, Utz
Abstract: Sacro‐coccygeal pilonidal sinus disease is classified as an asymptomatic, acutely abscess‐forming or chronic subcutaneous inflammation in the sacro‐coccygeal region featuring characteristic pits in the bottom cleft. Due to high rates of recurrence, two flap techniques have been established in the course of the past three decades. One of them is the Karydakis operation, the other option is a rotation flap named Limberg procedure. We report about a case of suture granuloma in the area of a Limberg flap after recurrent pilonidal sinus with extrusion of the suture material, thus mimicking recurrence. In case of recurrent pilonidal sinus following plastic coverage or primary closure, respectively, the differential diagnosis of suture granuloma should be considered.